Island Destination Image and Behavioural Intention: The Mediating Role of Destination Value Perception and Tourist Satisfaction - Haji, Sulfi Abdul; Sabuhari, Rahmat (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of this study was to analyse the effect of island destination image on behavioural intention with the mediating role of tourist satisfaction and perceived destination value. 150 domestic tourists who visited the ternate island destination were used as research samples. By using purposive sampling as a sampling technique. The results showed that the image of the island destination had an effect on tourist satisfaction and perceived destination value and had an impact on behavioural intention, but the destination image directly had an insignificant effect on behavioural intention, the results of this study also showed that tourist satisfaction and perceived destination value could play a mediating role.